The influence of buy-side analysts on mutual fund trading - Stefan Frey; Patrick Herbst (University of Cologne, Centre for Financial Research (CFR), 2010)
We present evidence of the impact of buy-side analysts on the behavior and performance of fund managers. Using data provided by a large global asset manager, we relate buy-side analysts' recommendations to fund transactions on a daily basis. Our results show that buy-side analysts have a significant influence on trading decisions: Fund managers almost certainly follow recent recommendation revisions in their trades. Fund flows and sell-side recommendations matter as well, but to a lesser extent. Positive abnormal returns to buy-side analysts' revisions are also reflected in the performance of mutual fund trades: trades triggered by buy-side recommendations have higher returns than other trades.
Keywords: G23; G11; G29; M41; 330; buy-side analysts; analyst recommendations; mutual funds; investment decisions; investment performance; Finanzanalysten; Anlageberatung; Investmentfonds; Führungskräfte; Anlageverhalten; Schätzung; Europa